Cultivating political powerhouses: TFA corps members experiences that shape local political engagement - Rebecca Jacobsen; Rachel White; Sarah Reckhow (Arizona State University, 2016)
In recent years, Teach for America (TFA) has invested in developing corps members as leaders. Although TFA asks corps members for a two-year commitment, TFA celebrates the achievements of alumni who have gone on to careers in politics, public policy, and advocacy. Thus, many community leaders see the arrival of TFA corps members as having a greater impact than just inside the classroom. While expectations for corps members are often high both from TFA and from the communities they serve, we seek to understand whether and how corps members become actively engaged in the broader political life of their placement city. Do corps members find the city fertile with opportunities to solve problems and engage in civic and political life? Or will these corps members leave their placements, viewing the political and educational challenges as intractable due to larger city politics? Using data from a panel study of 2012 corps members in four mid-sized city TFA placement sites, this study examines how attitudes towards and engagement with local politics shift as a result corps members' experiences. Our research indicates that commitments to local politics shift significantly. While some corps members report an increased commitment to local politics, a sizable group actually becomes less enthusiastic and involved. These shifts appear to be related to the perceived openness of the local political arena to newcomers, one's teaching placement and the local actions of TFA spin-off organization Leadership for Educational Equity (LEE).